Confocal laser endomicroscopy is a new imaging modality for recognition of intramucosal bacteria in inflammatory bowel disease in vivo. Issue 1 (27th October 2010) - Moussata, Driffa; Goetz, Martin; Gloeckner, Annabel; Kerner, Marcus; Campbell, Barry; Hoffman, Arthur; Biesterfeld, Stephan; Flourie, Bernard; Saurin, Jean-Christophe; Galle, Peter R; Neurath, Markus F; Watson, Alastair J M; et al.
Abstract : Background and objectives: Interaction of bacteria with the immune system within the intestinal mucosa plays a key role in the pathogenesis of inflammatory bowel disease (IBD). The aim of the current study was to develop a fluorescein-aided confocal laser endomicroscopy (CLE) method to visualise intramucosal enteric bacteria in vivo and to determine the involved mucosal area in the colon and ileum in patients with ulcerative colitis (UC) and Crohn's disease (CD). Methods: Initially, E coli strains expressing enhanced green fluorescent protein (pEGFP) were endomicroscopically imaged in mice. In addition, ex vivo and in vivo imaging of fluorescent human enteric bacteria was performed to specify the distinct endomicroscopic appearance of enteral bacteria. Targeted mucosal biopsies towards endomicroscopic identifiable intramucosal bacteria and negative mucosal areas were prospectively obtained during colonoscopy and correlated with bench-top fluorescence microscopy (FISH) to prove the endomicroscopic visualisation of intramucosal bacteria. Finally, a retrospective analysis as well as a prospective study was performed in patients with UC and CD to confirm the presence and distribution of intramucosal bacteria within the gut. Results: Confocal endomicroscopy was able to identify intramucosal pEGFP E coli in mice and strains of enteric microflora in the mucosa of humans. Using FISH as the gold standard, evaluation of 21 patients showed that CLE had a sensitivity of 89% and specificity of 100% to identify intramucosal bacteria. In a retrospective study, 113 patients with CD and UC had intramucosal bacteria significantly more often than 50 control patients (66% vs 60% vs 14%, p<0.001). This result was confirmed in a prospective study in which 10 patients with CD and 10 with UC had a significantly wider distribution of involvement with intramucosal bacteria in the colon and terminal ileum compared with 10 controls (85.2% vs 75.9% vs 16.8%, p<0.0001). Conclusions: CLE is a new tool that can image intramucosal bacteria in vivo in patients with IBD. Intramucosal bacteria are found more frequently and with a wider distribution in patients with IBD than in patients with a normal intestine.